1996
DOI: 10.3382/ps.0751393
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dietary and Injected Vitamin E for Poults

Abstract: An experiment was conducted to compare the efficacy of two dietary sources and an injectable form of vitamin E (VE) to improve the VE status of poults. Six of the treatments consisted of a factorial arrangement of three concentrations and two sources of dietary VE. Turkeys in these treatments received 12, 80, or 150 IU of either dl-alpha-tocopheryl acetate or d-alpha-tocopherol (d-alpha-TOC)/kg of diet. The seventh treatment consisted of a single subcutaneous injection of d-alpha-TOC at 1 d of age. Poults in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…At hatch, poults exhibit 144µg α-tocopherol /g liver and that this declines to just 5µg/g by 14d, although without apparent effect on health of non-stressed poults. Soto-Salanova and Sell (1996) did however show reduced susceptibility of RBCs to haemolysis when either injected with vitamin E or fed moderately high doses of vitamin E.…”
Section: Requirements For Sustaining General Bird Healthmentioning
confidence: 85%
See 1 more Smart Citation
“…At hatch, poults exhibit 144µg α-tocopherol /g liver and that this declines to just 5µg/g by 14d, although without apparent effect on health of non-stressed poults. Soto-Salanova and Sell (1996) did however show reduced susceptibility of RBCs to haemolysis when either injected with vitamin E or fed moderately high doses of vitamin E.…”
Section: Requirements For Sustaining General Bird Healthmentioning
confidence: 85%
“…Sell et al (1997) suggested that NRC (1994) levels of vitamin E are probably sufficient for growing turkeys that are "free of disease", even though previous studies from this group (Soto-Salanova and Sell, 1996) had shown that α-tocopherol stores in young poults are low and decline precipitously over the first 14d of life. An injection of 25 IU vitamin E or feeding diets with 150 IU vitamin E/kg tempered this decline, although did not eliminate it.…”
Section: Requirements For Sustaining General Bird Healthmentioning
confidence: 96%
“…One of the factors that prevents this disease is vitamin E. Its presence in the body reduces the amount of peroxides and free radicals (Scott, 1980;Sheffy and Williams, 1980). Supplementing diets with vitamin E above its requirement specified by poultry nutrition standards led to a greater concentration of α-tocopherol in the liver and blood serum in chickens (Soto-Salanova and Sell, 1994Sell, , 1996Młodkowski et al, 2002), in turkeys (Mallorino et al, 1992;Sell et al, 1997) and in laying hens (Cherian et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also indicated that the vitamin E status of turkey poults may be inadequate during the Ðrst 3 weeks after hatching (Sell 1996). A variety of approaches aimed at improving the vitamin E status of turkey poults have, in fact, been investigated ; these have included dietary supplementation of the poults with high levels of a-tocopherol (Applegate and Sell 1996), bile salts (Sotosalanova et al 1993), and fat (Sotosalanova and Sell 1995), as well as vitamin E injection (Sotosalanova and Sell 1996) and alterations in provision of n-6 and n-3 polyunsaturated fatty acids (Applegate and Sell 1996). The aim of the present study was to compare the concentrations of a-tocopherol and carotenoids in the maternal feed, the yolk and the tissues of the hatchlings for four avian species, namely the chicken (Gallus gallus domesticus), the turkey (Meleagris gallapavo), the duck (Anas platyrhynchos) and the goose (Anser anser).…”
Section: Introductionmentioning
confidence: 99%